Solving Thermal Radiation On Boundary Layer Flow Using BVP4 C Technique - MOHD KAMIL, ALEYA ASHIMA (Enhanced Knowledge in Sciences and Technology, 2022)
The purpose of this research is to analyse the effect of thermal radiation and Newtonian heating on boundary layer flow. A similarity transformation is used to transform the governing equation from partial differential equation to system of ordinary differential equation. The governing equations are then solved numerically by using shooting method with bvp4c. The numerical results of temperature profile and velocity profile are obtained by using MATLAB R2020b. The solution for the results is depends on four parameters which are Prandtl number, suction/blowing parameter, thermal radiation parameter and conjugate parameter. It is found that the value of wall temperature increases with the presence of thermal radiation and blowing parameter while it shows different behavior for the suction parameter effect.